FORENSIC MEDICINE AND INDIAN CRIMINAL LAWS - A STUDY OF RELEVANCY WITH LEGAL PROVISIONS - Duhan, Roshni (Innovare Journal of Medical Sciences, 2016)
Abstract: Forensic medicine is one of the largest and most important areas of forensic science. Also called legal medicine or medical jurisprudence, it applies medical knowledge to criminal and civil law. Areas of medicine that are commonly involved in forensic medicine are anatomy, pathology, and psychiatry. Medical jurisprudence or forensic medicine is the application of medical science to legal problems. It is typically involved in cases concerning blood relationship, mental illness, injury, or death resulting from violence. Autopsy is often used to determine the cause of death, particularly in cases where foul play is suspected. Post-mortem examination can determine not only the immediate agent of death but may also yield important contextual information, such as how long the person has been dead, which can help trace the killing. In medicolegal cases treatment gets priority. Thereafter procedural criminal law will operate in order to avoid negligent death.Â A doctor who is aware of the commission of crimes such as murder , dacoity, waging war against the lawful government, helping the escape of prisoners etc. is legally bound to report them to the nearest magistrate or police officer. The doctor having or reason to believe that an offence has been committed by patient whom he is treating intentionally omits to inform the police shall be punished. But if he treats a person who has attempted to commit suicide, he is not bound to report. Keywords: Forensic medicine, Police Inquest, Medical negligence, Indian Penal Code, Code of Criminal Procedure, Medicine and law